2002
DOI: 10.1016/s0893-133x(02)00286-5
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of BDNF mRNA in the Hippocampal Dentate Gyrus after Re-exposure to Cues Previously Associated with Footshock,

Abstract: This study examined the effects of footshock stress and reexposure to cues previously associated with footshock on expression of brain-derived neurotrophic factor (BDNF) mRNA in the hippocampus of male rats. Exposure to twenty 0.5-s 0.4-mA footshocks co-terminating withBrain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family of growth factors, which also includes nerve growth factor and neurotrophins 3 and 4. BDNF as well as these other neurotrophins, plays an important role in neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(119 citation statements)
references
References 57 publications
6
109
0
4
Order By: Relevance
“…In 1995, it was originally found that ADs increase the synthesis of BDNF (Nibuya et al, 1995). Later, several animal studies demonstrated that stress, an important factor in the etiology of depression, can decrease hippocampal BDNF levels (Smith et al, 1995;Nibuya et al, 1999;Rasmusson et al, 2002); conversely, chronic AD treatments could enhance BDNF expression in hippocampus (Larsen et al, 2008;Sillaber et al, 2008). Furthermore, infusion of BDNF into the midbrain or hippocampus induced AD-like effects in two separate depression models (Siuciak et al, 1997;Shirayama et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, it was originally found that ADs increase the synthesis of BDNF (Nibuya et al, 1995). Later, several animal studies demonstrated that stress, an important factor in the etiology of depression, can decrease hippocampal BDNF levels (Smith et al, 1995;Nibuya et al, 1999;Rasmusson et al, 2002); conversely, chronic AD treatments could enhance BDNF expression in hippocampus (Larsen et al, 2008;Sillaber et al, 2008). Furthermore, infusion of BDNF into the midbrain or hippocampus induced AD-like effects in two separate depression models (Siuciak et al, 1997;Shirayama et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence further suggests that BDNF may play a key role in the pathophysiology of stress-related disorders. Lower hippocampal BDNF levels have been found subsequent to various stressors such as prenatal stress (Fumagalli et al, 2004), footshock stress (Rasmusson et al, 2002), postnatal stress (MacQueen et al, 2003;Roceri et al, 2004) and restraint stress (Smith et al, 1995;Vaidya et al, 1997;Xu et al, 2004). Also of interest is the fact that intrahippocampal administration of BDNF protects against stress-induced impairments in spatial learning and memory and LTP (Radecki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RB101 produced an increase in ACTH levels that was not blocked by naltrindole. A variety of stressors and exogenously administered corticosterone have been shown to decrease BDNF mRNA expression in several brain regions, particularly the hippocampus (Rasmussen et al, 2002;Smith et al, 1995;Hansson et al, 2003). Therefore, the increase in stress hormones with RB101 might have the net effect of no change in BDNF.…”
Section: Discussionmentioning
confidence: 99%